Effect of Fish Water Waste Liquid Organic Fertilizer on Strawberry Flowering (Fragaria Sp) - Narita Amni Rosadi; Theresia Suzanna Catharina (Jurnal Penelitian Pendidikan IPA, 2022)
Strawberry plant (Fragaria sp) is one of the fruit plants grown in Indonesia, although it is not native to Indonesia. The growth of strawberry farmers continues to increase from year to year, especially those outside Lombok Island. This research was conducted at the Green house of the Jeruk Manis Farmer Group, Pejeruk Village, Mataram City. This research was conducted for 4 months starting from April 2022 to August 2022. This research was carried out experimentally using a complete randomized design with 6 treatments and 3 replications so that 18 experimental units were obtained, and each polybag consisted of 2 plants so that there were 36 plant units in total . The treatment given was the difference in concentration of POC fish waste water with concentrations (0.0, 1.5, 2.0, 2.5, 3.0, 3.5) ml/1 liter of water. Parameters observed were plant height (cm), number of leaves (strands), age of flowering, age of first harvest. The research results were analyzed statistically using variance. If the data obtained shows a real effect, a further test is carried out with Ducan's New Multiple Range Test (DNMRT) at the 5% level. Based on the results of the research that has been done, it can be concluded that the application of fish waste liquid organic fertilizer at a dose of 3.5 gives the best results on generative growth parameters.